Suppression of ferromagnetism in rippled La2/3Sr1/3MnO3 membrane with process-induced strain prepared by epitaxial lift-off technique - Kota Kanda; Ryuji Atsumi; Takamasa Usami; Takumi Yamazaki; Kohei Ueda; Takeshi Seki; Shigeki Miyasaka; Jobu Matsuno; Junichi Shiogai (APL Materials)
Transition metal oxides are a platform for exploring strain-engineered intriguing physical properties and developing spintronic or flexible electronic functionalities owing to the strong coupling of spin, charge, and lattice degrees of freedom. In this study, we exemplify the strain-engineered magnetism of La2/3Sr1/3MnO3 in freestanding and rippled membrane forms without and with process-induced strain, respectively, prepared by the epitaxial lift-off technique. We find that the deposition of the Pt/Ti stressor suppresses the crack formation in the lift-off process and induces a ripple structure in the La2/3Sr1/3MnO3 membrane. Laser micrograph and Raman spectroscopy show a ripple period of about 30 μm and a height of a few μm, where alternating convex and concave structures are subjected to a tensile strain of 0.6% and a compressive strain of 0.5%, respectively. While the freestanding La2/3Sr1/3MnO3 membrane exhibits room-temperature ferromagnetism, the macroscopic magnetic transition temperature (TC) of the rippled membrane is reduced by as much as 27%. Temperature-variable Kerr microscopy observation in the rippled membrane reveals that the spatial variation of TC is ∼4% of the macroscopic TC, which coincides with the local strains at convex and concave structures. The large reduction of macroscopic TC in the rippled membrane may be ascribed to the lattice disorders due to the strain gradient. Our demonstration of tuning ferromagnetism by the ripple structure validates the high potential of the process-induced strain in the epitaxial lift-off technique and paves the way for strain-mediated emerging physical properties in various transition metal oxides.